Phonon-Assisted Spin Current in a Hybrid System with a Single Molecular Quantum Dot System Applied with ac Magnetic Fields (Journal of Atomic and Molecular Sciences, 2012)
We investigate the spin current through a molecular quantumdot (MQD) irradiated with a rotating magnetic field and anoscillating magnetic field by nonequilibrium Green's function. Therotating magnetic field rotates with the angular frequency $ω_r$ around the $z$-axis with the tilt angle $θ$, and thetime-oscillating magnetic field is located in the z-axis with theangular frequency $ω$. Different behaviors have been shown inthe presence of electron-phonon interaction (EPI) which plays asignificant role in the transport. The spin current displaysasymmetric behavior as the source-drain bias $eV=0,$ novel side peaksor shoulders can be found due to the phonon absorption and emissionprocedure, and the negative spin current becomes stronger as theparameter $g$ increases. However, the spin currents display the samemagnitude and the same oscillation behavior in the region $μ_0B_1>3Δ$ regardless of the parameter $g.$